Variants of mtDNA among islanders of the lake Titicaca: highest frequency of haplotype B1 and evidence of founder effect - Sandoval, José (2004)
We analyzed mitochondrial DNA haplotypes from 144 samples of islanders of the Taquile and Amantani (Quechua speakers) and Los Uros and Anapia (Aymara speakers) of the Lake Titicaca, Peru. We have found the highest frequency of B1 mtDNA haplotype ever reported: 100% in Taquile (n= 57); 88,6% in Amantani (n= 35); 87,5% in Anapia (n= 24) and 75% in Los Uros (n= 28). There are other haplotypes but in low frequencies: 11,4% of C1 in Amantani; 17,9% of A2 and 7,1% of D1 in Los Uros; 4,2% of C1, C2 and D1 haplotypes in Anapia. The high frequency of the B1 haplotype indicates that Taquile, Amantaní and Anapia islands have been populated by a reduced founder group. Although the genetic affinity between islanders of Anapia and Los Uros, the proportion of some alleles in the latter suggest the persistence of the uru genetic background.